Inulin-type fructans improve active ulcerative colitis associated with microbiota changes and increased short-chain fatty acids levels - Valcheva, Rosica; Koleva, Petya; Martínez, Inés; Walter, Jens; Gänzle, Michael G.; Dieleman, Levinus A. (Gut microbes, 2019)
The intestinal microbiota is involved in ulcerative colitis (UC) pathogenesis. Prebiotics are hypothesized to improve health through alterations to gut microbiota composition and/or activity. Our aim was therefore to determine if inulin-type fructans induce clinical benefits in UC, and identify if benefits are linked to compositional and/or functional shifts of the luminal (fecal) and mucosal (biopsy) bacterial communities. Patients (n = 25) with mild/moderately active UC received 7.5 g (n = 12) or 15 g (n = 13) daily oral oligofructose-enriched inulin (Orafti®Synergy1) for 9 weeks. Total Mayo score, endoscopic activity and fecal calprotectin were assessed. Fecal and mucosal bacterial communities were characterized by 16S rRNA tag sequencing, and short chain fatty acids (SCFA) production were measured in fecal samples. Fructans significantly reduced colitis in the high-dose group, with 77% of patients showing a clinical response versus 33% in the low-dose group (P = 0.04). Fructans increased colonic butyrate production in the 15 g/d dose, and fecal butyrate levels were negatively correlated with Mayo score (r = −0.50; P = 0.036). The high fructan dose led to an increased Bifidobacteriaceae and Lachnospiraceae abundance but these shifts were not correlated with improved disease scores. In summary, this pilot study revealed that 15 g/d dose inulin type fructans in UC produced functional but not compositional shifts of the gut microbiota, suggesting that prebiotic-induced alterations of gut microbiota metabolism are more important than compositional changes for the benefits in UC. The findings warrant future well-powered controlled studies for the use of β-fructans as adjunct therapy in patients with active UC.